Initiation and changes in use of social media for peer support among young adult cancer patients and survivors. Issue 11 (3rd July 2021) - Lazard, Allison J.; Collins, Meredith K. Reffner; Hedrick, Ashley; Horrell, Lindsey N.; Varma, Tushar; Love, Brad; Valle, Carmina G.; Benedict, Catherine
Abstract: Purpose: Social isolation is a prominent challenge for many young adults with cancer. Despite desires for peer‐to‐peer connections through technology, little is known about how young adults initiate or use social media for support over time. Methods: We interviewed young adults with cancer ( n  = 45; age 18–39, in or post cancer treatment) to explore their initiation of social media for support, changes in use over time, and types of connections sought. Results: Young adults with cancer learn about online support through individual personal recommendations, advocacy organizations, or searching on Google or social media. Most were reluctant to use social media support initially because of feeling overwhelmed—from diagnoses, abundance of online information, or demands of participation—and joined when informational and emotional needs arose. Many wished they had joined earlier. Some participants use social media to make close connections while others simply want to "see" others' shared experiences or crowdsource information. Conclusion: Young adults with cancer often haphazardly find online support from personal recommendations or Internet searches. Desires for social media connections are not one‐size‐fits‐all; there are important audience segmentations for the degree and type of peer support. Implications for Cancer Survivors: Better promotion of online social support options and benefits—early in one's cancer timeline and systematically through healthcare providers, cancer organizations, or family and friends—could improve access to helpful peer‐to‐peer support.